2021
DOI: 10.1016/j.jmsy.2020.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing and the COVID-19 challenges: An in-depth study

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) rapidly achieved global pandemic status. The pandemic created huge demand for relevant medical and personal protective equipment (PPE) and put unprecedented pressure on the healthcare system within a very short span of time. Moreover, the supply chain system faced extreme disruption as a result of the frequent and severe lockdowns across the globe. In such a situation, additive manufacturing (AM) becomes a supplementary manufacturing process to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 71 publications
0
74
1
2
Order By: Relevance
“…3D printing or additive manufacturing (AM) is a digital manufacturing process, in which the materials are added layer by layer to create 3D objects directly from the computer-aided design (CAD) models [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. 3D printing has gained significant popularity in the last two decades due to a number of appealing advantages such as the limitless design freedom and capability to produce low cost and multifunctional objects with highly delicate/complex structures in a short period of time [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…3D printing or additive manufacturing (AM) is a digital manufacturing process, in which the materials are added layer by layer to create 3D objects directly from the computer-aided design (CAD) models [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. 3D printing has gained significant popularity in the last two decades due to a number of appealing advantages such as the limitless design freedom and capability to produce low cost and multifunctional objects with highly delicate/complex structures in a short period of time [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they suggested that polypropylene fibers may be released to the environment due to the mechanical stresses induced by water bodies. Tareq et al [ 5 ] argued that 3D-printed facemasks may solve the solid waste crisis associated with the single use facemasks because most of the 3D-printed facemasks were made from thermoplastic polymers that can be recycled. However, after several recycling cycles, these 3D printed masks will become solid waste that can release microplastic fibers to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…For the computation of deformation in a structure, we need to model the material's response by means of a constitutive equation, also called the material model. Since additive manufacturing is using a layer-by-layer technique, there is an added inner structure related material response [31][32][33][34]. Finite element method (FEM) is the standard approach in solid bodies for computing structural response under mechanical loading.…”
Section: Introductionmentioning
confidence: 99%